2003
DOI: 10.1001/jama.290.9.1157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Communications Training on Medical Student Performance

Abstract: ESPITE WIDESPREAD ACknowledgment of the importance of improved patientphysician communication, 1,2 teaching of communications skills has not been systematically integrated into most medical school curricula 3,4 and has not been subjected to evaluation across different schools. 5 Furthermore, few standardized assessment instruments specifically measure students' communications performance. [6][7][8] METHODS InterventionThree medical schools-New York University, University of Massachusetts, and Case Western Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
240
1
33

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(283 citation statements)
references
References 39 publications
5
240
1
33
Order By: Relevance
“…[20][21][22][23][24] In addition, many of these training efforts have been confined to specific populations [25][26][27][28][29][30][31][32] or have been with trainees. [33][34][35][36][37] To date, more complex interventions and/or courses aimed at specific conditions have shown the greatest likelihood of improving patient experience. 19 To our knowledge, this is the first study of a communication skills training intervention implemented for all physicians in a large multispecialty setting, and which uses CMS' measures of patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] In addition, many of these training efforts have been confined to specific populations [25][26][27][28][29][30][31][32] or have been with trainees. [33][34][35][36][37] To date, more complex interventions and/or courses aimed at specific conditions have shown the greatest likelihood of improving patient experience. 19 To our knowledge, this is the first study of a communication skills training intervention implemented for all physicians in a large multispecialty setting, and which uses CMS' measures of patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…A vizsgálat során standar dizált pácienssel végzett klinikai interjúkat rögzítettek videóra, s a felvételeket egy kommunikációs készségeket leíró skála segítségével elemezték. Eredményeik szerint a kommunikációoktatásban részesült orvostanhallgatók a kapcsolatépítéstől kezdve az anamnézis felvételén át a te rápiás lehetőségek megbeszéléséig több területen is szig nifikánsan jobb kommunikációs teljesítményt nyújtottak, mint a képzésben még nem részesült társaik [13].…”
Section: "A Kommunikációt Nem Lehet Tanulni a Jó Kommunikációs Készsunclassified
“…Several studies have shown that teaching ethics, empathy and communication skills improves the quality of the doctor-patient relationship (Hafferty and Franks 1994;Caldicott and Danis 2009;Yedidia et al 2003;Eriksson et al 2007;Eckles et al 2005). The literature also shows that humanities disciplines in the medical curriculum are necessary for humanistic education but are not sufficient.…”
Section: Introductionmentioning
confidence: 99%